Археологічні пам’ятки Любеча - Веремейчик, Олена (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2023)
The archaeological heritage of Liubech (Lyubech, Chernihiv region, Ukraine) includes various monuments and objects from the Bronze Age to early Modernity (2000 BC – 17th century) with small time gaps. Archaeological surveys in Liubech began in the late 19th century and have continued until today with certain interruptions. Despite the close attention paid by scholars to the archaeological monuments of Liubech, it should be noted that the area of the city within its administrative boundaries (both the floodplain part of the Dnieper River and the densely developed part of the town) has not been sufficiently studied.